Managing cultural festivals : tradition and innovation in Europe - Salvador, Elisa, 1977-; Pedersen, Jesper S. (Jesper Strandgaard), 1959- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book aims at renewing the attention on a niche field, Cultural Festivals, so important for valorizing cultural traditions and local heritage visibility as well as social well-being. Following the disruptive consequences of the COVID-19 pandemic, this fragile sector deserves more attention from public authorities and stakeholders at national and European levels with a suitable and dedicated plan of recovery and valorization. This book provides a comparative analysis of Cultural Festivals in Europe, taking insights from an international range of high-level scholarly contributors. Individual chapters highlight and analyse challenges around the organisation, management and economics of Cultural Festivals. As a whole, the book provides a comprehensive overview of scholarly research in this area, setting the scene for the future research agenda. Matters related to educational programs and new audience development, as well as challenges related to sustainability solutions, are also included. The book employs a tradition versus innovation lens to help readers account for the consequences of the digital revolution, new audience development, and the sustainability agenda. The result is a book which will be valuable reading for researchers, academics and students in the fields of event and cultural management and beyond"--
OCLC-licensed vendor bibliographic record.
Keywords: Festivals -- Europe -- Management; Festivals -- Europe -- Planning; Europe -- Social life and customs; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism